Kontestasi Media Digital: Analisis Tagar #BubarkanMUI versus #DukungMUI - Arif, Moch. Choirul; Ariza Qurrata A’yun (Jurnal Komunikasi Islam, 2023)
The study aims to explain the role of the hashtags #BubarkanMUI and #DukungMUI in getting support for digital opinion, and the comparison of the hashtags #BubarkanMUI. The results have revealed, first, the importance of hashtags in the digital opinion movement (DMO). This success is based on the narration of tweets that are uploaded more emotionally. Second, the digital opinion movement carried out by the hashtags #bubarkanMUI and #supportMUI is a movement that occurs spontaneously, unorganized, homogeneous, and has many actors involved within the movement. Third, the hashtags #bubarkanMUI and #dukungMUI generally use the same pattern: (a) in terms of thematic aspects, although some posted tweets do not describe the two hashtags, (b) schematic aspects or sentence structure, tweets posted on both hastags unwell- structured, (c) the meanings of the posted tweets show the side of disappointment (#bubarkan MUI) and a defense of the existence of MUI (#dukungMUI ), so the impression of the two hashtags is contesting to win public opinion.